A Perspective on Research on Kyosei (living harmoniously): with reference to UNESCO activities - KAWANOBE, Satoshi (Journal of Kyosei Studies, 2012)
This report is based upon the lecture delivered at Toyo University on January 8, 2011.UNESCO, pursuing peace and human well-being, has engaged in many activities in the field ofeducation since its establishment in 1946. This report picks out and explains UNESCO’s four maintopics in the field of education: international understanding, environment education, life-longlearning and inclusive education. It also briefly discusses the thoughts described in LearningSociety by R. Hutchins, Learning to Be (UNESCO, 1973) and others. Through examining theseworks, it suggests with some observations three main subjects which we need to study further inour research activities. These are: how to live as an individual aiming at living harmoniously; how tokeep good relationship with other people and/or groups; and how to cope with global and societalchallenges such as preservation of natural environment and helping people suffering fromdifficulties.